Reuse of malaria rapid diagnostic tests for amplicon deep sequencing to estimate Plasmodium falciparum transmission intensity in western Uganda - Boyce, Ross M.; Hathaway, Nick; Fulton, Travis; Reyes, Raquel; Matte, Michael; Ntaro, Moses; Mulogo, Edgar Mugema; Waltmann, Andreea; Bailey, Jeffrey A.; Siedner, Mark J.; Juliano, Jonathan J. (Scientific reports, 2018)
Molecular techniques are not routinely employed for malaria surveillance, while cross-sectional, community-based parasite surveys require significant resources. Here, we describe a novel use of malaria rapid diagnostic tests (RDTs) collected at a single facility as source material for sequencing to esimtate malaria transmission intensity across a relatively large catchment area. We extracted Plasmodium falciparum DNA from RDTs, then amplified and sequenced a region of the apical membrane antigen 1 (pfama1) using targeted amplicon deep sequencing. We determined the multiplicity of infection (MOI) for each sample and examined associations with demographic, clinical, and spatial factors. We successfully genotyped 223 of 287 (77.7%) of the samples. We demonstrated an inverse relationship between the MOI and elevation with individuals presenting from the highest elevation villages harboring infections approximately half as complex as those from the lowest (MOI 1.85 vs. 3.51, AOR 0.25, 95% CI 0.09–0.65, p = 0.004). This study demonstrates the feasibility and validity of using routinely-collected RDTs for molecular surveillance of malaria and has real-world utility, especially as the cost of high-throughput sequencing continues to decline.
Keywords: Malaria; Amplicon; Plasmodium falciparum